Supervision of Financial Reporting Through the Prism of the Regulatory Framework and Practice in the Republic of Serbia - Milutinović, Sunčica; Medved, Ivana (Industrija, 2017)
The paper presents the research in the field of internal supervision in financial reporting in the private sector of the Republic of Serbia. In the first part of the paper, legal regulations and current international regulations are compared. The aim of this study was to evaluate the achieved level of harmonization between the national and international regulatory framework in the field of financial reporting. The second part of the paper presents the analysis of the effect of the internal supervision in financial reporting on comparability of financial statements in terms of consistent application of the regulatory framework. The study aimed at examining whether internal supervision affects the comparability of financial statements. The methodology of the research that was used in the processing of data obtained through the questionnaire consisted of One-Factor Analysis of Variance, Pearson's correlation coefficient, and Spearman's and Kendall's rank correlation coefficient. The sample included 297 employees working on accounting and/or audit positions of the private sector of the Republic of Serbia. The results showed a (partial) non-compliance of domicile regulations with EU regulations, i.e. that the national regulatory framework is not harmonized with international regulatory framework. In addition, the results indicated that the internal supervision, defined both in domicile and EU regulations, contributes to the comparability of financial statements in terms of consistent application of the regulatory framework.
Keywords: Comparability; Harmonization; Regulatory framework; Financial reporting; Internal supervision; Regulation